2008
DOI: 10.1209/0295-5075/82/47005
|View full text |Cite
|
Sign up to set email alerts
|

Exact Haldane mapping for all S and super universality in spin chains

Abstract: PACS 73.43.Cd -Quantum Hall effects: Theory and Modelling PACS 75.10.Jm -Quantized spin models PACS 11.10.Kk -Field theory in dimensions other than four Abstract. -The low energy dynamics of the anti-ferromagnetic Heisenberg spin S chain in the semiclassical limit S → ∞ is known to map onto the O(3) nonlinear σ model with a θ term in 1+1 dimension. Guided by the underlying dual symmetry of the spin chain, as well as the recently established topological significance of "dangling edge spins," we report an exact … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…The same behavior has recently been found in strong coupling studies of closely related two dimensional models of the instanton vacuum. 61 Analogous to Eq. (327) one therefore expects that βθ = a ln σ ′ xx (328) in the limit where σ ′ xx goes to zero.…”
Section: A Robust Quantization Of Hall Conductancementioning
confidence: 99%
“…The same behavior has recently been found in strong coupling studies of closely related two dimensional models of the instanton vacuum. 61 Analogous to Eq. (327) one therefore expects that βθ = a ln σ ′ xx (328) in the limit where σ ′ xx goes to zero.…”
Section: A Robust Quantization Of Hall Conductancementioning
confidence: 99%
“…non-linear sigma model in two dimensions it was shown that the ϑ vacuum generally displays massless excitations that propagate along the confining "edge" of the system [1][2][3][4][5]. This new aspect of the sigma model has come in many ways as a welcome surprise.…”
Section: Super Universality In a Series Of Investigations On The Grasmentioning
confidence: 99%
“…In applications to quantum A.M.M. Pruisken ( ) Institute for Theoretical Physics, University of Amsterdam, Valckenierstraat 65, 1018 XE Amsterdam, The Netherlands e-mail: pruisken@science.uva.nl spin liquids [6,7], for example, the edge excitations describe the dynamics of the "dangling" quantum spins located at the "edges" of the spin chain [4,5]. In the context of quantum Hall liquids [8][9][10][11][12], on the other hand, these excitations are identically the same as those described by the theory of "chiral edge bosons" [2,3].…”
Section: Super Universality In a Series Of Investigations On The Grasmentioning
confidence: 99%
See 1 more Smart Citation
“…For a single spin, the first term in the Berry phase in Eq. 7 can be written in the following way 59 ,…”
Section: Appendix A: Berry Phasementioning
confidence: 99%